Korelasi Perhatian Orang Tua Terhadap Kemandirian Belajar Siswa Kelas IV Sekolah Dasar - Anindita Brillianti Purwaningrum; Nur Fajrie (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this research was to examine the correlation between parents’ attention to the learning independence of fourth grade students of elementary school. This research used quantitative approach that applied correlation design. This research used saturated sample technique with the number of respondens 115 students. Data collection technique used questionnaires and interviews. The instrument test used validity test and reliability test. This research used descriptive statistical analysis, initial data analysis, and final data analysis. Initial data analysis used normality test, linearity test, multicollinearity test. Final data analysis used simple correlation test, double correlation test, significance test, simple regression analysis, and multiple regression analysis. The result showed that there were positive and significant correlation between parents attention to the learning independence, with 0,701 count rate > count table which included in strong category and contribute of 49,1%. The conclusion of this research that there were positive and significant correlation between parents’ attention to the learning independence.